PENGARUH HARGA, IKLAN DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE TOKOPEDIA (STUDI KASUS PADA PENGGUNA TOKOPEDIA DI KABUPATEN DEMAK) - Anggreani, Irvana Ayu; Yuliati, Yuliati (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This study aims to determine the effect of price, advertising, and brand image on purchasing decisions for e-commerce users in Demak Regency. The population in this study were Tokopedia e-commerce users in Demak Regency. The sampling technique used is non-probability sampling technique with a purposive sampling technique. The sample of this study were 97 respondents, Tokopedia e-commerce users in Demak Regency. Data collection using a questionnaire. The data analysis used is multiple linear regression analysis using the help of the SPSS application.The results of this study indicate that 1) Price has a positive and significant effect on purchasing decisions with a t-count value of 2,568 > t-table 1,986 and sig. 0,020 < 0,05; 2) Advertising has a positive and significant effect on purchasing decisions with a t-count value of 2,363 > t-table 1,986 and sig.0,020 < 0,05; 3) Brand image has a positive and significant effect on purchasing decisions with a t-count value of 6,902 > t-table 1,986 and sig. of 0,000 < 0,05; 4) Price, Advertising, and Brand image simultaneously affect purchasing decisions with an F-count value of 35,377 > F-table 3,309 and sig. of 0,000 < 0,05. Keywords: Price, Advertising, Brand Image, Purchasing Decisions